APLIKASI ZERO-ONE GOAL PROGRAMMING DALAM MASALAH PEMILIHAN PROYEK PEMASARAN - Silalahi, Bib Paruhum; Pertiwi, Silviana Eka; Mayyani, Hidayatul; Aliatiningtyas, Nur (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Marketing management is an activity to plan and organize marketing activities in order to achieve organizational or company goals efficiently and effectively. Problems arise when there are several or many different projects that can be implemented as company marketing projects. These projects are usually categorized by several objectives. These goals can be complementary or contradictory. In operation, decision-makers are required to choose and determine the right project to achieve the target. In this paper, we discuss a programming model using the zero-one goal programming approach, a selection of marketing projects to meet many objectives and constraints, and then give examples of its implementation. Discussion and implementation include goal programming categories: nonpreemptive goal programming and preemptive goal programming